Induction of immunosuppressive functions and NF-κB by FLIP in monocytes - Alessandra Fiore (Nature Portfolio, 2018)
Signaling and transcriptional regulation of MDSC activity remains largely undefined. Here the authors show that monocytic MDSC immunosuppression is triggered by c-FLIP and requires NFκB, implicate this axis in cancer prognosis and response to therapy, and employ ectopic FLIP to treat immunopathology.